A Simple Protocol for the Determination of Lysostaphin Enzymatic Activity - Alexander V. Grishin; Svetlana V. Konstantinova; Irina V. Vasina; Nikita V. Shestak; Anna S. Karyagina; Vladimir G. Lunin (MDPI AG, 2020)
Antibacterial lysins are enzymes that hydrolyze bacterial peptidoglycan, which results in the rapid death of bacterial cells due to osmotic lysis. Lysostaphin is one of the most potent and well-studied lysins active against important nosocomial pathogen Staphylococcus aureus. Similarly to most other lysins, lysostaphin is composed of enzymatic and peptidoglycan-binding domains, and both domains influence its antibacterial activity. It is thus desirable to be able to study the activity of both domains independently. Lysostaphin cleaves pentaglycine cross-bridges within the staphylococcal peptidoglycan. Here, we report the protocol to study the catalytic activity of lysostaphin on the isolated pentaglycine peptide that is based on the chromogenic reaction of peptide amino groups with ninhydrin. Unlike previously reported assays, this protocol does not require in-house chemical synthesis or specialized equipment and can be readily performed in most laboratories. We demonstrate the use of this protocol to study the effect of EDTA treatment on the lysostaphin enzymatic activity. We further used this protocol to determine the catalytic efficiency of lysostaphin on the isolated pentaglycine and compared it to the apparent catalytic efficiency on the whole staphylococcal cells. These results highlight the relative impact of enzymatic and peptidoglycan-binding domains of lysostaphin on its bacteriolytic activity.